Implementasi Literasi Sekolah dalam Meningkatkan Kemampuan Membaca Siswa Kelas 4 SD Swasta Islam Nursyamsiani - M. Khairil Fadli; Rina Devianty; Muhammad Syaifullah (Concept: Journal of Social Humanities and Education, 2024)
of literacy activities in improving the reading ability of fourth grade students at Nursyamsiani Islamic Private Elementary School. How to implement literacy activities in improving students' reading skills and what are the obstacles and solutions in implementing the school literacy. The purpose of this research is to describe the process of implementing Literacy Activities in Improving the Reading Ability of Class IV Students at Nursyamsiani Islamic Private Elementary School. This type of research is qualitative with a descriptive approach. The subjects of this research are school principals, teachers, fourth grade students and other school members. The complete documents in this research are documents related to literacy activities such as infrastructure, literacy activity processes, and other teaching tools. There are 3 data collection techniques in this research, namely, interviews, observation and documentation. Based on research conducted, the implementation of School Literacy activities has a very important role in improving the reading ability of fourth grade students at the Nursyamsiani Islamic Private Elementary School.